Perlindungan Hukum Tenaga Kerja Non-Kontraktual: Studi tentang Perjanjian Pemborongan Jasa Konstruksi - Syafik, Muhamad; , Dr. Nurhadiantomo; , Wardah Yuspin, S.H.,M.Kn.,Ph.D (2017)
This study aims to reveal and analyze the legal protection for workers in chartering agreement under employment law, and trying to find ways to guarantee and protect the non-contractual labor of construction services in case of accidents. This is a qualitative research, with a sociological juridical approach. Secondary data and primary data, which collected using observation, interviews and document studies, were analyzed using an interactive data analysis process. The results of this study, among others, 1) there were some legal protection for workers under employment law, such as working time, job safety and health, wages, and welfare. 2) Protection for non-contractual labor in case of accidents, if the worker was injured at work or got occupational disease, was a program participant of work accident insurance and life insurance (JKK and JKM) BPJS Employment, then they get a health care in accordance to the needs for medic and compensation in the form of money, and if not a participant of JKK and JKM of BPJS employment, then depends on the employer kindness and policies, which can provide compensation in the form of money or not, with the amount of compensation varies according to the worker's special skill. Keywords: Chartering Aggreement, Legal Protection, Outsourcing.